Methodologies comparison for design of paired drip laterals on uniformly sloping fields - Galvão, Ícaro Monteiro; Guimarães, João de Jesus [UNESP]; Avilez, Alberto Mario Arroyo [UNESP]; Saad, João Carlos Cury [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2020)
This work aimed to compare different methodologies for designing paired laterals of drip irrigation systems on uniformly sloping fields. For this purpose, the methodologies proposed by Keller e Bliesner (1990), Jiang e Kang (2010), and Monserrat; Barragan e Cots (2018) were evaluated. The length of uphill and downhill lateral lines, distribution uniformity (DU), flow, and pressure variations were calculated for both topographic conditions. The Keller e Bliesner (1990) methodology generated the best design for paired laterals, with the lowest DU difference between the uphill and downhill sections; also, the flow variation remained under the 10% limit. The second-best performance was obtained by the method of Monserrat; Barragan e Cots (2018). Jiang e Kang (2010)’s procedure was the least adequate, generating a 10.9% flow variation in the uphill section.
Comparação entre metodologias para dimensionamento de linhas laterais pareadas de gotejamento em desnível
Keywords: Drip irrigation; Hydraulic; Uniformity